Corrosion behavior of Fe amorphous/Al-12Si piston composites with core-shell structure - Yingdong Wang; Zuxiang Lin; Chengzhou Liu; Deyong Zhao; Chunqiong Li; Yuan Wang (Scientific Reports)
Abstract The current piston material, Al-12Si, lacks sufficient passivation in the acidic lubrication system of biodiesel engines, making it prone to corrosion in the presence of Cl−. Fe amorphous particles exhibit good compatibility with Al-12Si, possessing strong corrosion resistance, excellent passivation ability, and good high-temperature stability. They are a potential reinforcement for enhancing the Al-12Si piston material. Fe amorphous/Al-12Si core-shell structural composites (FACS) were synthesized through ball milling and hot extrusion. The composites’ composition, microstructure, and elemental distribution were characterized by X-ray diffraction, optical microscopy, and EDS spectroscopy. To accelerate the evaluation process, Potentiodynamic polarization and Electrochemical impedance spectroscopy were used to study the electrochemical corrosion behavior. By analyzing the self-corrosion current density (icorr), self-corrosion potential (Ecorr), polarization resistance, inductance, admittance absolute value (Y0), and diffusion coefficient (n), the mechanism of Fe amorphous particle doping in enhancing the corrosion resistance of Al-12Si was discussed. The research results indicate that: The Fe amorphous particles, during ball milling and hot extrusion at 440 °C, do not recrystallize and maintain their good passivation ability. Spherical Fe amorphous particles act as “balls bearings” during hot extrusion, enhancing flowability and promoting the formation of a core-shell structure FACS with uniform composition distribution, high relative density, and low porosity when doping with 2–10% Fe amorphous particles. This prevents the formation of local potential differences, making the potential on the alloy surface more uniform, which helps reduce the risk of galvanic corrosion and improves corrosion resistance. However, when the doping content of Fe amorphous particles reaches 20%, excessive doping particles squeeze and rub against each other during hot extrusion, leading to amorphous agglomeration, low relative density, and high porosity defects in the resulting FACS, which causes uneven potential, increases local potential differences, and reduces corrosion resistance. Compared to Al-12Si, FACS doped with 2–10% Fe amorphous particles shows a decrease in icorr from 254.66 µA/cm2 to 114.98 µA/cm2, and an increase in Ecorr from 766.89 mV to 794.78 mV, indicating a reduced corrosion rate with the doping of an appropriate amount of Fe amorphous particles. As the doping content of Fe amorphous particles increases from 2 to 10%, the polarization resistance increases, indicating improved corrosion resistance; the inductance increases, suggesting that corrosion primarily occurs at the surface; Y0 increases, and n decreases, indicating a reduction in the depth of the corrosion reaction, and the stability of the surface protective oxide film is improved. However, when the doping content of Fe amorphous particles reaches 20%, the opposite effect occurs, and the corrosion resistance of the FACS decreases. Notably, FACS with 10% Fe amorphous particles exhibited the strongest corrosion resistance, making it a potential candidate for biodiesel engine pistons.